2013
DOI: 10.1371/journal.pone.0073684
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Copper Acquisition by Developing Murine Mesothelioma: Decreasing Bioavailable Copper Slows Tumor Growth, Normalizes Vessels and Promotes T Cell Infiltration

Abstract: Copper, an essential trace element acquired through nutrition, is an important co-factor for pro-angiogenic factors including vascular endothelial growth factor (VEGF). Decreasing bioavailable copper has been used as an anti-angiogenic and anti-cancer strategy with promising results. However, the role of copper and its potential as a therapy in mesothelioma is not yet well understood. Therefore, we monitored copper levels in progressing murine mesothelioma tumors and analyzed the effects of lowering bioavailab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…To this day, the anti-angiogenic potential of metal starvation represents a major research target in the field of clinical oncology. In fact, in vitro and in vivo studies on cancer models indicate that copper deprivation may not act directly on the tumour cells, but on the local vasculature, thereby cutting off nutrients to proliferating cancer cells [8,235]. However, it is not clear whether copper limitation prevents the growth of tumour blood vessels through the inhibition of endothelial cell proliferation or if it just affects the regularity of neo-formed structures.…”
Section: Copper and Angiogenic Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…To this day, the anti-angiogenic potential of metal starvation represents a major research target in the field of clinical oncology. In fact, in vitro and in vivo studies on cancer models indicate that copper deprivation may not act directly on the tumour cells, but on the local vasculature, thereby cutting off nutrients to proliferating cancer cells [8,235]. However, it is not clear whether copper limitation prevents the growth of tumour blood vessels through the inhibition of endothelial cell proliferation or if it just affects the regularity of neo-formed structures.…”
Section: Copper and Angiogenic Diseasesmentioning
confidence: 99%
“…However, it is not clear whether copper limitation prevents the growth of tumour blood vessels through the inhibition of endothelial cell proliferation or if it just affects the regularity of neo-formed structures. In this sense, it is noteworthy that HUVECs, an election model for in vitro angiogenic studies, continue to replicate in the presence of trientine and TM (tetrathiomolybdate) copper-chelating agents, and that passive copper reduction by penicillamine only induces slight, but not significant proliferation [8,235]. Accordingly, dietary regimens including copper-chelating agents (penicillamine, trientine or TM) in a mesothelioma mouse model demonstrated that the anti-angiogenic and tumour-suppressive action is due to the normalization of blood vessels, functional for sustaining CD4 + T cell infiltration into the tumour microenvironment, but not anti-proliferative effects [235].…”
Section: Copper and Angiogenic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given between meals, TM is absorbed into the blood, and forms complexes with serum copper and albumin, reducing the bioavailable copper. [76] A phase II trial examined a combination of D-pen and a low-copper diet in human glioblastoma multiforme (ClinicalTrials.gov Identifier: NCT00003751). [48,[67][68][69][70][71][72][73][74] A small phase II clinical trial showed that the event-free survival for 75 advanced breast cancer patients with TM-treatment was 75.6% at a median followup of 6.9 years (ClinicalTrials.gov Identifier: NCT00195091).…”
Section: Copper Depletion Therapymentioning
confidence: 99%
“…[75] D-Pen depletes copper by binding free copper in blood and tissues, forming a stable soluble complex that is excreted in urine. [76] A phase II trial examined a combination of D-pen and a low-copper diet in human glioblastoma multiforme (ClinicalTrials.gov Identifier: NCT00003751). The serum copper levels fell to the desired level of <50 µg dL −1 after 2 months of therapy.…”
Section: Copper Depletion Therapymentioning
confidence: 99%